Analysis of the application of the principle of innovation to the persons of violent criminal actions that committed together in public (Decision Study No. 227/Pid.B/2022/PN Kwg) - Aryo Fadlian; Muhamad Dyshrul Anwar (IHSA Institute, 2022)
The principle of presumption of innocence has a very significant correlation with the principle of human rights because in essence it is application of the concepts of human rights recognition, respect, and protection. Everything that can be achieved and accomplished via action. if the state is actually founded on the rule of material law and a democratic state, and the constitution guarantees the existence of these principles. To ensure that the suspect's human rights are respected, protected, and recognized, and that justice and the law are upheld, the Indonesian Criminal Code must establish and regulate the principle of presumption of innocence. The implementation of criminal justice can result in legal order and legal certainty. This study aims to determine how decision no. 227/Pid.B/2022/PN Kwg influences the application of the presumption of innocence against individuals who commit violent crimes together in public; displays the judge's evaluation of the decision and consideration of the legal decision no. 227/Pid.B/2022/PN Kwg; the research method is normative law analysis.